An unusual asymmetric pseudomacrocyclic free base ligand and nickel(II) chelate: X-ray crystallographic and DFT studies. (9th March 2017) - Bhikraj, Sandipa; Munro, Orde Q.; Akerman, Matthew P.
Graphical abstract: A unique asymmetric pseudomacrocryclic dipyrrolidequinoxaline-based ligand and the nickel(II) chelate have been synthesised and characterised. The solid state structures of both have been elucidated; these X-ray data show the ligand to be in an interesting zwitterionic configuration. DFT methods were used to delineate the experimental data and probe the energies of possible canonical forms. Abstract: A novel tetradentate dipyrrolidequinoxaline ligand, 5-(3-5-[( E )-(propylimino)methyl]-1 H -pyrrol-2-ylquinoxaline-2-yl)-1 H -pyrrole-2-carbaldehyde (H2 L1) and its Ni(II) complex, 2-[3-(5-formyl-1 H -pyrrol-2-yl)quinoxaline-2-yl]-5-(prpylimino)methyl]propyl-1-ide nickel(II), [Ni(L1)], have been synthesised and studied by X-ray crystallography. The asymmetric pseudomacrocyclic ligand, which has an unusual NN ′ N ″ O donor atom set, crystallised in the orthorhombic space group P 21 21 21 . Interestingly, the X-ray data show that the ligand is present as a zwitterion in the solid state with the trans imine and pyrrole N-atoms protonated. The zwitterionic structure leads to two intramolecular hydrogen bonds with hydrogen bond lengths (D⋯A) for Npyrrole –H⋯Npyrrole and Nimine –H⋯Oaldehyde which measure 2.591(2) and 2.836(2) Å, respectively. The Ni(II) chelate crystallises in the monoclinic space group Cc and adopts a square planar coordination geometry. DFT-simulated structures of both H2 L1 and [Ni(L1)] in vacuo are in good agreement with those obtained experimentally in the solid state with RMSDs of 0.1710 Å and 0.3214 Å, respectively. DFT studies showed that the experimentally determined zwitterionic structure ofH2 L1 is significantly lower in energy than the other possible canonical forms. ESP maps provide insight into the hydrogen bonding patterns of the ligand. TD-DFT calculations were used to delineate the experimental UV–Vis spectra.